Le mie prigioni : (selections) ; and, Francesca da Rimini / Pellico ; edited by Kenneth McKenzie. - Pellico, Silvio, 1789-1854. (Tufts University. Tisch Library., 2020)
1 online resource (168 pages, 2 unnumbered leaves of plates) : illustrations.; Half-title: The Heath-Chicago Italian series.; Tisch In-House Digitization 2020-01-27